The Influence of Work Competence and Discipline on the Performance of Planning Agency Employees - Hipzi Rahmadin Noor; Mujahid Mujahid; Nurmadhani Fitri Suyuthi (Newinera Publisher, 2023)
This research aims to determine the influence of competence and work discipline on the performance of North Penajam Paser Regency Planning, Research and Development Agency employees. This research suspects that there are two things that influence employee performance, namely lack of effective communication and competence. This is because ideally employees work in accordance with their competencies, but in the North Penajam Paser Regency Planning, Research and Development Agency office, employees are still found who work not in accordance with their competencies. Apart from that, employee discipline is also expected to be a factor in their performance. In this research, researchers found many problems related to official discipline. In this research, the data collection method used was a saturated sampling technique and multiple linear regression analysis with the help of the SPSS 26 program which was used to analyze the data. The research results show that the competency variable (X1) has a positive and significant effect on employee performance (Y). However, there is a positive and significant influence of the discipline variable (X2) on employee performance (Y). The results of the coefficient of determination (41.5%) show that the ability of the independent variables (competence and work discipline) in explaining the dependent variable (employee performance) is in a small percentage and there are still other variables that are not included in this research.